Examining artificial intelligence (AI) technologies in marketing via a global lens: Current trends and future research opportunities - Kopalle, Praveen K.; Gangwar, Manish; Kaplan, Andreas; Ramachandran, Divya; Reinartz, Werner; Rindfleisch, Aric (International journal of research in marketing, 2022)
•Examine AI technologies in marketing via a global lens.•Global lens focuses on three levels of analysis: country, company, and consumer.•Country-level analysis emphasizes the heterogeneity in economic inequality across countries.•Company-level analysis focuses on glocalization.•Consumer-level analysis examines consumer ethics and privacy concerns in relation to AI. Artificial intelligence (AI) has captured substantial interest from a wide array of marketing scholars in recent years. Our research contributes to this emerging domain by examining AI technologies in marketing via a global lens. Specifically, our lens focuses on three levels of analysis: country, company, and consumer. Our country-level analysis emphasizes the heterogeneity in economic inequality across countries due to the considerable economic resources necessary for AI adoption. Our company-level analysis focuses on glocalization because while the hardware that underlies these technologies may be global in nature, their application necessitates adaptation to local cultures. Our consumer-level analysis examines consumer ethics and privacy concerns, as AI technologies often collect, store and process a cornucopia of personal data across our globe. Through the prism of these three lenses, we focus on two important dimensions of AI technologies in marketing: (1) human–machine interaction and (2) automated analysis of text, audio, images, and video. We then explore the interaction between these two key dimensions of AI across our three-part global lens to develop a set of research questions for future marketing scholarship in this increasingly important domain.